Noctura / Muhammad Zikri Amni Mohd Isa - Mohd Isa, Muhammad Zikri Amni (Universiti Teknologi MARA, Kedah, 2025)
This final portfolio project explores innovative transport design tailored for wildlife conservation. "Noctura" is a conceptual motorcycle designed to support wildlife researchers by addressing the challenges of light and noise pollution that threaten nocturnal habitats. The project combines advanced functionality with a deep respect for natural ecosystems. "Noctura" features a compact design for easy navigation through dense environments, low-light technology to preserve dark skies and protect nocturnal species, and noise reduction to minimize disturbances in sensitive areas. These features work together to create a vehicle that seamlessly integrates into wildlife research settings, offering a tool that aids researchers while prioritizing environmental harmony. The name "Noctura" symbolizes a commitment to preserving the tranquility of the natural world. It reflects the project’s mission to blend mobility with conservation, ensuring that research activities can proceed without compromising the delicate balance of ecosystems. This design reimagines transport not just as a means of movement but as a contributor to the preservation of our planet. "Silent Mobility for Wildlife Conservation" is more than a tagline—it’s a call to innovate responsibly and to create designs that respect the natural world. With "Noctura," we move toward a future where technology and nature coexist in harmony.